PLACENTAL INSUFFICIENCY IN COMPLICATED PREGNANCY AND POSSIBILITY OF TREATMENT WITH DIPYRIDAMOLE - A. D. Makatsariya; V. O. Bitsadze; D. Kh. Khizroeva; I. V. Khamani (Акушерство, гинекология и репродукция, 2017)
Placental insufficiency is an acute or chronic process leading to progressive deterioration in placental function and a decrease in transplacental transfer of oxygen and nutrients to the fetus. The resulting fetal hypoxemia is hypoxia and reduction in fetal growth with abnormal neurodevelopment during childhood as outcome. Current approaches in classification, diagnostics and management of placental insufficiency in women with complicated pregnancy are presented in the review article. Treatment of placental insufficiency includes antiplatelet agents, low molecular weight heparins and vitamin and mineral supplementation. Dipyridamole is most preferred antiplatelet agents that could be prescribed in I-III trimesters. Proper preconception can help to prevent placental insufficiency in women with respective risk-factors.